The British monarchy : the changing role of the royal family - Horning, Nicole (World history (Lucent Press), 2020)
Traces the British monarchy through history, discussing its kings, queens, and changing role over time. Also discusses the current popularity of the British monarchy and the Windsors. Includes a timeline, photographs, primary sources, and further resources.